Hubungan Kualitas Bagian Pendaftaran Dengan Kepuasan Pasien Ibu Hamil Rawat Jalan Di Puskesmas Pembantu Dataran Tinggi Kelurahan Dataran Tinggi Kota Binjai Tahun 2023 - Parningotan Simanjuntak; Nopalina Suyanti Damanik; Hafizah pandiangan; Armando Joshua Siburian (Journal of Educational Innovation and Public Health, 2023)
Service quality can be measured by comparing the perceptions between expected services and services received and felt by patients. Patient satisfaction is the level of patient feelings after comparing with his expectations. A patient if he is satisfied with the value provided by a product or service then it is very likely to become a customer for a long time. The purpose of this study was to analyze the relationship between service quality in the registration section and patient satisfaction for pregnant women at the highlands sub-district, Binjai sub-district health center, Kota Binjai in 2023. The type of research used in this study was analytic with a cross-sectional approach. Cross sectional is a research approach that emphasizes the time of measurement/observation of independent variable data and depends only once at a time. The chi-square test results obtained a p value of 0.0050.005. This means that there is a significant relationship between the quality of the registration section and the satisfaction of pregnant women. Reliability where the p value = 0.000. Responsiveness with p value = 0.000. Assurance with a p value = 0.000. Empaty with p value = 0.002.